Propuesta de una guía de adecuaciones curriculares para estudiantes con inteligencia limítrofe del Centro Educativo Básico General Presidente Roosevelt - García de Paredes Estripeaut, Ana Mercedes (2020)
The purpose of this investigation was to find a way to help students with Borderline Intelligence. The investigation is named Proposal for the Elaboration of Curricular Adaptations for Students with Borderline Intelligence in the school Centro Educativo Básico General Presidente Roosevelt. The main idea is to develop a guide that includes Curricular Adjustments for students with Borderline Intelligence, then we will train part of the teachers in the school on how to use the guide and apply it in different scenarios, and finally (but is not included in our investigation) the application of this guide with the students who need it. Through a survey we discover that some school teachers don’t know how to make curricular adjustments, for that reason they are not applying them to the students who need them. There are some students with Borderline Intelligence in the school, and after we train the teachers we would like to see if there are any improvements with the students.